Political connections, bailout in financial markets and firm value - Banerji, Sanjay; Duygun, Meryem; Shaban, Mohamed (Elsevier, 2016)
The paper shows that politically motivated interventions in the financial market in the form of bailing out borrowing firms reduce banks’ incentives to gather valuable information about firms’ projects. This loss of information is a hidden cost which adversely affects firm value. Firms invest resources and pay a premium to politically connected persons (BOD or other personnel). Such connections serve the twin purposes of hedging and enhancement of the value of collateral pledged against bank loans. Feeling secured, banks lose incentives to monitor borrowing firms. Thus, wealth effect of bailout from political connection is partially offset by the losses of valuable information brought about by bank lending. In equilibrium, the trade-off from gains out of political connections and costs due to losses from information-based bank monitoring depend on (i) the country’s disclosure laws, (ii) the political environment, (iii) the premium paid to form connections, and (iv) the state of the economy.